PREDICTION OF CARBON DIOXIDE EMISSION FROM ELECTRICITY GENERATION IN ASEAN - Meiri Triani; Kania Dewi; Addina Shafiyya Ediansjah (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2023)
The Coal-Fired Power Plants with low-emissions plants in the power sector can avoid nearly 800 million tonnes CO2 by 2030. The number of populations, Gross Domestic Product (GDP), electricity generation, NDC, and relevant energy policies influenced the prediction of Carbon Dioxide (CO2) emission from electricity generation. Aim: The objective is to analyze trends of CO2 growth related to electricity generation activities from countries in ASEAN with an emphasis on identifying the factors that influence it and evaluating the effectiveness of existing decarbonization policies in AMS and developing suitable strategies to reduce future CO2 emissions. Methodology and Result: Predicting CO2 emissions is conducted using three approaches by considering the newest NDC and energy policies, conducted by descriptive and quantitative analysis based on secondary data of (1) general information on ASEAN Member States (AMS), (2) information on power plants, (3) information on fuel use in electricity generation, and (4) decarbonization policies in AMS. Results indicated that the availability of potential energy sources (coal/oil/gas/RE) influences the dominant energy used in AMS Prediction of CO2e emission in the 2020 to 2040 period identified Vietnam as one of the highest CO2e emitters (380,1 Mt CO2e) in the electricity sector by 2030. Conclusion, significance and impact study: AMS needs to make a more aggressive energy policy to reduce CO2 level significantly, achieving the 2050 net zero transition targets. Ultimately, the shifting from coal-fired electricity plants to other fuel sources with a lower emission factor proves to be the most significant factor towards emission reduction.